Thin for good : - Pescatore, Fred (John Wiley & Sons, 2000)
Taking low-carb diets to the next level, Thin for Good combines clinically tested, up-to-the-minute nutritional advice with an added bonus: a revolutionary mind-body program designed to eliminate your cravings. Leading you through the eleven emotional levels of eating, Dr. Pescatore shares his unique solutions to the psychological roadblocks we all face when trying to lose weight. The result is a thirty-day plan–filled with affirmations, self-evaluations, and exercises–that will get you on the road to lifelong thinness. Customized for your sex and stage of life, filled with delicious recipes and meal plans, Thin for Good gives you the fuel you need for your lifestyle. Get thin for good–now and forever.